Microsatellites from Lysiphlebus hirticornis Mackauer (Hymenoptera: Braconidae), a specialist primary parasitoid attacking the specialist tansy aphid, Metopeurum fuscoviride Stroyan (Hemiptera: Aphididae) - Nyabuga, Franklin N.; Wolfgang, W. Weisser; Loxdale, H. D. (My University, 2008)
Nine polymorphic microsatellite loci were isolated from the specialist aphid parasitoid, Lysiphlebus hirticornis. In addition, two published loci from closely related Lysiphlebus species were also used. Allelic diversity and heterozygosity were quantified in samples collected from eight tansy plants growing in an area of approximately 150m2 in Jena, Germany.
Keywords: aphid parasitoid; Braconidae; DNA; Lysiphlebus hirticornis; microsatellites